2016
DOI: 10.1002/2016je005188
|View full text |Cite
|
Sign up to set email alerts
|

Water generation and transport below Europa's strike-slip faults

Abstract: Jupiter's moon Europa has a very young surface with the abundance of unique terrains that indicate recent endogenic activity. Morphological models as well as spectral observations suggest that it might possess shallow lenses of liquid water within its outer ice shell. Here we investigate the generation and possible accumulation of liquid water below the tidally activated strike‐slip faults using a numerical model of two‐phase ice‐water mixture in two‐dimensional Cartesian geometry. Our results suggest that gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 75 publications
2
59
0
Order By: Relevance
“…; Kalousová et al, 2016;Neveu et al, 2015;Quick & Marsh, 2016;Showman et al, 2004). Future models could examine more complex chemical systems, melt transport through fractures, and Rayleigh-Taylor instabilities, as well as the influence of topographically induced pressure gradients (cf.…”
Section: Discussionmentioning
confidence: 99%
“…; Kalousová et al, 2016;Neveu et al, 2015;Quick & Marsh, 2016;Showman et al, 2004). Future models could examine more complex chemical systems, melt transport through fractures, and Rayleigh-Taylor instabilities, as well as the influence of topographically induced pressure gradients (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The fate of these putative melt pockets is, however, difficult to determine. For such shallow depths, it is possible that part of the melt reaches the surface (Lesage et al, 2020;Mitri et al, 2008;Showman & Han, 2004), while most of the melt probably sinks to the subsurface ocean via percolation through the solid ice matrix (Kalousová et al, 2014(Kalousová et al, , 2016. The occurrence of these melt pockets may therefore favor material exchange between the subsurface ocean, the ice layer, and potentially the surface.…”
Section: Occurrence Of Meltingmentioning
confidence: 99%
“…Studies that leverage numerical predictions of mid-ocean ridge evolution to interpret observed seafloor morphology have illuminated the processes of melting and deformation and identified key controls on seafloor morphology and faulting (e.g., Behn & Ito, 2008;Buck et al, 2005;Howell et al, 2016;Olive et al, 2015;Tian & Choi, 2017). brittle layer (lithosphere) for simplified rheologies (e.g., Mitri & Showman, 2005), and of melt migration beneath imposed tectonic features (Kalousová et al, 2016). brittle layer (lithosphere) for simplified rheologies (e.g., Mitri & Showman, 2005), and of melt migration beneath imposed tectonic features (Kalousová et al, 2016).…”
Section: Introductionmentioning
confidence: 99%